Review Artikel : Sifat Fisik Bahan Pengikat Tablet Hisap - Anisa Anisa; Jenni Getbriela T; Mifta Dewi; Nor Tiara Sari; Siti Fatimatuzzahra; Nor Latifah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The purpose of lozenges is to allow the tablet to dissolve in stages in the mouth. Lozenges are solid preparations consisting of more than one pharmaceutical chemical, the base material is flavored, and the taste is sweet. Binders are important excipients, especially when making lozenges, because they increase intragranular and intergranular strength, forming tablets that meet the required physical qualities. The purpose of this review paper is to gather data about the physical characteristics of lozenge binders. Based on the literature study conducted, binders of lozenges namely Gelatin, CMC-Na, Hydroxypropyl Methyl Cellulose (HMPC), Jackfruit Seed Starch and Durian Seed Starch affect the physical properties of lozenges.